Floating green: creating design guidelines for artificial floating islands as social green spaces along urban waterfronts - Borelli, Taryn (Kansas State University, 2019)
An artificial floating island (AFI) is a man-made, floating planter installed with aquatic or terrestrial plants. AFIs float by a constructed, buoyant frame or substrate mat, and can be anchored in place via cables or piers. AFIs float on the surface of water, allowing plant roots to be constantly submerged in the water column. Through rhizofiltration, AFIs filter excess nutrients and pollutants from the water. For centuries, AFIs have been used for ecological purposes and have supported agriculture and human habitation. Recently, AFIs have been growing in usage and popularity for their ecological benefits, and some contemporary AFI designs incorporate spaces for social and recreational activities. Although these AFI designs successfully address their primary environmental goals, they may not fully accommodate the social and recreational uses of public open spaces. This research focuses on how AFIs can support social and recreational activities while maintaining their existing ecological services and contextual appropriateness. Through a series of precedent studies, expert interviews, and projective design, the research will inform new guidelines for the design of social and recreational AFIs, and ultimately help develop a new type of public green space.
Keywords: Artificial Floating Island; Landscape Architecture; Guidelines; Waterfronts; Floating; Public Green Space